Scientific essentialism - Ellis, Brian (New York : Cambridge university press, 2001)
Ellis defends the idea that the fundamental laws of nature are grounded in the essential properties of the things they govern. He argues that our world is dynamic, made up of transient objects that are in constant interaction with one another.
Part I. Concepts: 1. Concepts of scientific essentialism; Part II. Ontology: 2. Natural kinds; 3. Powers and dispositions; Part III. Scientific Explanation: 4. Realism and essentialism in science; 5. Essentialism in the social sciences; Part IV. Laws of Nature: 6. Theories of laws of nature; 7. Natural necessity; Part V. The New Essentialism: 8. The essentialist program
Keywords: Essence - Philosophy; Science - Philosophy